IMPLEMENTASI MANAJEMEN STRATEGIC PENDIDIKAN MADRASAH DI MIN 1 KULONPROGO YOGYAKARTA - Irwanto Irwanto (Jurnal Terapung : Ilmu - Ilmu Sosial, 2022)
This study aims to examine the implementation of educational strategy management in Madrasah MIN 1 Kulonprogo. This research is a case study research that is qualitative in nature, data is collected through in-depth observation and interviews and documentation. The results showed that the implementation of strategic management carried out by MIN 1 Kulonprogo involved all madrasah stakeholders, the madrasah first formulated the madrasa vision and mission by conducting a swot analysis. Followed by determining the target to be achieved, then followed by determining the strategy that will be used by the madrasa for the realization of all the quality targets that have been formulated and agreed. The implementation of the strategy carried out at MIN 1 Kulonprogo is by creating a team of each field to carry out all the strategies that have been made in the form of programmed and measurable activities. The evaluation used by MIN 1 kulonprogo is to hold a weekly formal meeting.Keywords: Implementation; strategic management; Educational institutions